AAGBS sharing session: writing for Q1 journals - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2020)
The AAGBS sharing session, hosted by the Arshad Ayub Graduate Business School (UiTM), took place on 9 September 2020. The session, conducted via Cisco Webex, focused on "Writing for Q1 Journals" featuring speaker Associate Professor Dr. Roslina Ab. Wahid (Associate Professor of Quality Systems, Arshad Ayub Graduate Business School).